Cytogenetics of six Brazilian species of Psocoptera - Zefa, Edison [UNESP]; Fontanetti, Carmem Silvia [UNESP]; Mesa, Alejo [UNESP] (Sociedade Brasileira de Genética, 1996)
The karyotypes of the following six species of Brazilian Psocoptera are reported: Caecillius sp. (Caecillidae), Triplocania ? caudata New (Ptiloneuridae), Brachinodiscus cf. lepidus (Banks) (Psocidae), Psococerastis interrupta New (Psocidae), Ptycta nr reticulata New (Psocidae) and Trichadenotecnum sinuatum New (Psocidae). All of them had males with 2n = 17 and an XO sex determining mechanism.
Keywords: cytogenetics; Psocoptera